Malnutrition and Pressure Injury Risk in Vulnerable Populations: Application of the 2019 International Clinical Practice Guideline. (March 2022) - Munoz, Nancy; Litchford, Mary; Cox, Jill; Nelson, Jeffrey L.; Nie, Ann Marie; Delmore, Barbara
Abstract : ABSTRACT: Nutrition plays a vital role in promoting skin integrity and supporting tissue repair in the presence of chronic wounds such as pressure injuries (PIs). Individuals who are malnourished are at greater risk of polymorbid conditions, adverse clinical outcomes, longer hospital lengths of stay, PI development, and mortality, and incur increased healthcare costs compared with patients who are adequately nourished. In addition, some patient populations tend to be more vulnerable to PI formation, such as neonates, patients with obesity, older adults, and individuals who are critically ill. Accordingly, this article aims to review the latest nutrition care recommendations for the prevention and treatment of PIs, including those recommendations tailored to special populations. A secondary objective is to translate nutrition recommendations into actionable steps for the healthcare professional to implement as part of a patient plan of care. Implementing an evidence-based plan of care built around individualized nutrition interventions is an essential step supporting skin integrity for these populations. The 2019 Prevention and Treatment of Pressure Ulcers/Injuries: Clinical Practice Guideline (CPG) affirms that meeting nutrient requirements is essential for growth, development, maintenance, and repair of body tissues. Many macronutrients and micronutrients work synergistically to heal PIs. Registered dietitian nutritionists play an important role in helping patients identify the most nutrient dense foods, protein supplements, and oral nutrition supplements to meet their unique requirements.